A study on the spawning season of 3 \(Acropora\) species in Nha Trang bay, Southern waters of Vietnam - Vo Si, Tuan; Ho Son, Lam; Dang Tran, Tu Tram; Phan Kim, Hoang; Doan Van, Than; Mai Xuan, Dat (Vietnam Journal of Marine Science and Technology, 2022)
Specimens for the study on coral spawning of three species were collected at two sites in Nha Trang bay, South Vietnam, in 2014, 2015, 2016, 2018 and 2019. The determination of spawning seasons was based on observations of gonadogenesis development of A. florida and A. robusta and variation of egg average sizes of these two species and A. hyacinthus. Data analysis and comparative discussions allow us to assume that the 3 Acropora species exhibited single cycle spawning annually and their spawning period occurred in March/April between the full moon and crescent moon. However, their maturity periods were not the same, starting before and ending after the full moon for A. florida and A. robusta but starting after the full moon and lasting until the crescent moon for A. hyainthus. Further studies are needed to improve the understanding of coral spawning and support coral restoration using sexual reproduction.